Intelligent alarm system for hospitals using smartphone technology - Bashar S. Bashar; Marwa M. Ismail (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
During the last decade, attention was paid to detect the accident and call the ambulance as soon as possible, the situation was neglected after the arrival of the patient to the specified service point. This negligence led to an increase in the mortality rate, especially where the highest percentage of deaths occurred during the first hour after the accident. This highest Mortality can be avoided by providing proper health care after the arrival of the patient to the hospital, the proposed system reduces the rescue time after the arrival of a patient to the hospital, and it requires each hospital to be endowed with a reception model responsible for detecting and reporting accident situations to the emergency service. It was be found that there is an urgent need for a web-based hospital management system with a mobile web service to respond immediately to incidents in the event of an accident. This system utilizes the Android phone application to connect to the server for transferring the specified data to the hospital and it can be used for comprehensive accident analysis and management. In this paper, a combination of Android phone application, database, and visual studio 2012 was used to develop the system.